Exploring the impact of Instagram like visibility on self-confidence - Susilawaty, Fera Tri; Jaya, Asrul; Sudirman, Faturachman Alputra; Halika, La Ode Herman (Jurnal Kajian Komunikasi, 2023)
Background: Instagram allegedly hid the number of likes due to its alleged negative effect. However, it now allows users to choose their visibility settings. Users can either hide or show the number of likes, which has become a conversation topic among users. Some users responded positively, while others had less favorable responses. Moreover, because they consider the “like” feature one of Instagram’s key differentiators, some users hide the number of likes while others continue to display them. Purpose: This study explores users’ choices in configuring Instagram-like settings and their underlying motivations. Additionally, the study also examines the role of Instagram-Likes in boosting self-confidence. Method: This research used a quantitative descriptive method involving 703 students from the Communication Science Study Program at Halu Oleo University, Indonesia. The sample consisted of 70 individuals aged 18 to 24. The data analysis used descriptive statistics to provide a general overview of each variable, displayed with a frequency chart. Researchers also used qualitative data for comparative purposes to enhance research results. Result: Most respondents chose to indicate the number of likes, categorizing their motives into neutral, positive, and negative categories. Instagram likes are a relatively insignificant aspect of life. On the positive side, they can offer benefits to users, such as validation and recognition. Conversely, flaunting one’s likes can be viewed as seeking validation or showing off. It is worth noting that some individuals who conceal the visibility of likes do so to safeguard their self-esteem and mental well-being. Another finding from this study is that Instagram-Like can strengthen their self-confidence. Conclusion: Instagram users have complete control over the Instagram-like options that allow them to hide their like count or not. Instagram-Like can increase self-confidence. The consideration of ‘likes’ as a manifestation of praise, appreciation, acceptance, admiration, and love from others is a prevailing sentiment among individuals. Implication: The researchers expect this research will provide new insights into using social media wisely for positive mental health.